Kajian Sistematic Implementasi Hypnoparenting Dalam Pengasuhan Anak Usia Dini - Dahlia Dahlia; J Andree Eko Nugroho; Willie Japaries (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Child is a picture of the future for the family, both and bad character of the child in the future is a reflection of the education received in childhood in the family. Therefore, parents strive to provide good education, nurturing and balanced nutrition for their growth and development. All of that can be done by applying the best method to children in their golden age. One parenting method that parents can use is hypnoparenting. Hypnoparenting is educating children by giving positive suggestions in order to form a good personality and morals. The purpose of this writing is to explain the concept of hypnoparenting to help parents in parenting at an early age. Methods used in This research is a literature review with data sources obtained from scientific journals and research reports related to the problem.